ЛОТИН ТИЛИ ТИББИЁТ ТЕРМИНОЛОГИЯСИНИНГ БОЙИШ МАНБАСИ СИФАТИДА - Акбарходжаева, Ф.А. (SCIENCE and SOCIETY, 2021)
Latin, as the language of science, had a great influence on the terminology of special scientific fields. The emergence of scientific terms based on Latin continues to this day, indicating the constant interest of linguists in the lexicon of this field. Indeed, in the works of foreign and domestic linguists, much attention is paid to the problem of learning Latin mastery. Indeed, the Latin language serves as a basis for the creation and formation of medical terms.
Keywords: medical terms; vocabulary; Latin; assimilation; terminology; concept